Dawid Bunikowski and Alan D. Hemmings (eds.), Philosophies of Polar Law (New York: Routledge, 2021) - Jonathan Wood (Nordicum-Mediterraneum, 2021)
A review of the book: Dawid Bunikowski and Alan D. Hemmings (eds.), Philosophies of Polar Law (New York: Routledge, 2021)